Case studies of three geological archives for rare radionuclide measurements using accelerator mass spectrometry - Fichter, Sebastian; Koll, Dominik; Rolofs, Annabel; Wallner, Anton (Frontiers in Environmental Chemistry, 2024)
Long-lived radionuclides in our environment provide important information on natural and anthropogenic processes. Their presence and concentration reflect the balance of production and decay. Geological archives store such information and the nuclides can be chemically extracted from the bulk sample. Accelerator mass spectrometry (AMS) represents a sensitive method to quantify those nuclides at natural levels. Three different terrestrial archives are discussed here as examples for radionuclide extraction using various chemical separation methods for subsequent AMS measurements. We focus on sample preparation for the cosmogenic radionuclides 10 Be and 26 Al, various anthropogenic actinide isotopes such as U, Pu and Am as well as the astrophysically interesting nuclides 41 Ca, 53 Mn and 60 Fe. The processed materials cover samples with masses between a few mg and up to a few hundred kg and protocols are presented for the quantitative extraction of some 10,000 atoms of cosmogenic or interstellar origin per sample and even as low as a few hundred actinide atoms.